Selenium alleviates Staphylococcus aureus-induced mastitis by modulating mitochondrial dynamics and inhibiting the ROS/NLRP3/Pyroptosis pathway - Xue Qi; Yanjun Hu; Jinghan Yang; Mingxuan Jiang; Junhao Zhang; Yanting Du; Changmin Hu (Molecular Biology Reports, 2026)

Unveiling TWC replacement benefits in in-use vehicles from a concentration-reactivity-toxicity perspective - Jie Yao; Xinping Yang; Yongdong Wang; Jian Wang; Yanjun Wang; Chao Peng; Hongfei Chen; Xin Li; Yunjing Wang; Yan Ding (Environmental Pollution, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Pollutant removal and herbal biomass production using a rooftop-deployable hydroponic floating island system for purification tank effluent treatment - Yanjun Wu; Suqing Wu; Mian Zhang; Pu Yang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2026)

Linking source-specific heavy metal contamination to probabilistic health risks in urban river sediments: Evidence from PMF and land use analysis - Shuhan Yang; Weijie Zhao; Hui Qian; Panpan Xu; Yixin Liu; Yanjun Shen; Yongqi Zang; Qiming Wang; Zhiming Cao (Journal of Environmental Chemical Engineering, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

Balancing active hydrogen species flux via spillover enables efficient dilute-nitrate electroreduction to ammonia in a neutral medium - Chenghao Yang; Chang Shen; Yanjun Chen; Xin Xiao; Xiaoping Gao; Wanglai Cen; Mengyang Fan; Jianjun Li; Jinyu Liu; Jing Li (Chemical Engineering Journal, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

pH-Shifting combined with heat treatment regulates the aggregate structure and interfacial functional properties of egg white protein microparticles powder - Yating Wu; Yicheng Guo; Junhua Li; Luping Gu; Yanjun Yang; Cuihua Chang; Yujie Su (Food Research International, 2026)

Bioactive orientin-loaded Janus adhesive hydrogel promotes macrophage polarization and gastric injury repair - Yanqi Li; Yang Su; Huawu Yang; Maoyuan Zhao; Wangshuo Yang; Zhenxing Wang; TongTong Zhang; Jie Chen; Yanjun Liu; Lu Liu; Jinhao Zeng (Chemical Engineering Journal, 2026)

Geochemical and hydrological controls on aragonite versus calcite precipitation in speleothems and paleoclimatic implications - Rui Zhang; Haiwei Zhang; Christoph Spötl; Carlos Pérez-Mejías; Zixin Guan; Heather Stoll; Yanjun Cai; Liangcheng Tan; Fudong Wang; Xunlin Yang; Yan Yang; Lijuan Sha; et al. (Chemical Geology, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Mechanism of EPFRs formation from hydroquinone on transition metal oxide surfaces: coupled experimental and density functional theory study - Junyao Fu; Lingqin Zhao; Aijia Zhang; Guohao Yang; Fan Yu; Yanjun Hu (Waste Disposal & Sustainable Energy, 2026)

Kinetic mechanism and structural evolution during blank roasting of vanadium-bearing shale - Xiaolong Yu; Jianping Jin; Xinran Zhu; Zhe Bai; Shuaihou Yang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Activated carbon-quartz sand dual-layer filter material accelerates the start-up of filter: Performance and mechanism - Sen Yang; Dong Li; Hongpeng Li; Jifang Zheng; Yanjun Zhu; Sibo Fu; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2026)

Natural acid-based quaternary ammonium ionic liquid biphasic systems for sustainable recovery of gold(I) thiosulfate from electronic waste leachate - Yanjun Chen; Qihang Lu; Yi Liu; Hao Xiang; Wenjing Chen; Fan Lei; Shixiong Wang; Xiangjun Yang (Journal of Environmental Chemical Engineering, 2026)

Seasonal-Spatial Hydrochemical Variations and Salinity Control Mechanisms of Shallow Groundwater: Insights from the Northern Piedmont of the Qinling Mountains, China - Yixin Liu; Hui Qian; Panpan Xu; Xiaoxin Shi; Siqi Li; Yanyan Gao; Weijie Zhao; Shuhan Yang; Zhiming Cao; Jie Chen; Yanjun Shen (Journal of Environmental Sciences, 2026)

Morphodynamic adjustments of the Lower Yangtze River during 1988–2023: Integrated effects of sediment reduction and rocky outcrops - Lei Zhang; He Qing Huang; Hui Li; Zhongwu Jin; Chao Guo; Peng Yang; Yanjun Wang; Tianwei Qian (Geomorphology, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Greener cities, cleaner homes: Evaluating the effect of China's low-carbon city pilot policy on urban household energy consumption structure - Yunchang Wang; Yanjun Ren; Jieyu Yang; Mi Zhou; Qiran Zhao (Energy Policy, 2026)

Stimulating sulfur metabolism by overexpression of Sulfide:quinone reductase in Acidithiobacillus caldus coupled with low pH-high S0 integrated strategy in chalcocite bioleaching - Ruian Ji; Mingwei Wang; Xingyu Huo; Yiwen Zhu; Zhidong Guo; Yingming Wang; Jia Wang; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2026)

Molten salt-assisted Co-pyrolysis of biomass and waste plastics: Analysis of product characteristics - Yanjun Hu; Chong Yang; Fan Yu; Qianqian Guo; Xingxuan Zhang; Wei Bao; Kitae Baek; Rufei Lu; Frederik Ronsse (Biomass and Bioenergy, 2026)

A near-infrared fluorescent probe lights up protective carbon monoxide during inflammation in live systems - Sihang Lv; Longyang Yang; Changjian Wu; Yangtian Liu; Yanjun He; Yuyao Cao; Pengfu Li; Zhongchang Wang; Hai-Liang Zhu (Analytica Chimica Acta, 2026)

A high-strength interpenetrating-network cotton-derived biochar aerogel: Coupling uranium(VI) removal and interfacial solar desalination - Yang Wang; Yun Wang; Yang Li; Yanjun Du; Hao Jiang; Ruiyang Chang; Xingnong Wu; Yan Liu; Dingzhong Yuan; Xiaoyan Li (Process Safety and Environmental Protection, 2026)

A few-shot fault diagnosis method for ship motors based on multi-source data and multi-view task guidance - Yuan Xu; Deqiang He; Chunyang Dai; Zhenzhen Jin; Yanjun Chen; Yang Fu (Ocean Engineering, 2026)

Corrigendum to “Integrative phylogenetics and geography unveil Quaternary diversification and mitochondrial-nuclear discordance in Odorrana schmackeri sensu lato (Anura, Ranidae): Roles of Qinghai-Tibetan uplift, climate oscillations, and asymmetric gene flow”. [Mol. Phylogenet. Evol. 216 (2026) 108528] - Yanjun Zhu; Zhuo Chen; Yuxiao He; Xinyue Yang; Xiaofei Zhai; Qiuya Wang; Xiaohong Chen; Xiang Ji (Molecular Phylogenetics and Evolution, 2026)

Bioaerosol emissions during initial food waste degradation: Emission dynamics, dispersion modeling, and health risk assessment - Yingchao Liu; Qiange Tang; Yanjun Liu; Zhanhong Yang; Jianbing Wang (Journal of Hazardous Materials, 2026)

Enhancing nattokinase stability through synergistic interactions:Construction and mechanism analysis of multi-level encapsulation structures in fig-like gel beads - Yao Cheng; Yanjun Tong; Shanjun Tao; Shiqi Zhang; Han Jiang; Ruijin Yang (Food Research International, 2026)

Development of OSA (N, O)-acylated chitosan edible coatings loaded with cinnamon essential oil for strawberry preservation - Shiqi Zhang; Tingyi Zhou; Juncai Leng; Han Jiang; Yanjun Tong; Ruijin Yang (Food Hydrocolloids, 2026)

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sophaline B inhibits non-small cell lung cancer by activating NLRP3/caspase-1/GSDMD-dependent pyroptosis and PI3K/AKT/mTOR-mediated autophagy - Yibo Hou; Zhongfu Wang; Yang Wu; Ting Deng; Siyu Yang; Shaohua Ma; Yubo Zhang; Ding Luo; Yanjun Chen; Xiaoyong Dai (Natural Product Research, 2026)

Effect of environmental factors and the photodegradation of methylene hygromycin in actual water samples by Pr3+-doped bismuth tungstate - Min Zhou; Lanfang Ma; Yanyan Wang; Yanjun Fang; Rongying Yang; Fujun Liu (Journal of Water Process Engineering, 2026)

High internal phase emulsions stabilized by milk protein-arabinoxylan-quercetin ternary complex: Enhanced environmental stability and fat digestive property (Milk protein-AX-Q complex-stabilized HIPEs: Stability and digestion) - Xuenan Gao; Peizhu Liu; Sirong Li; Olayemi Eyituoyo Dudu; Yanjun Li; Yan Li; Hongfang Yang; Jinju Cheng; Tingsheng Yan (Journal of Food Engineering, 2026)

Synergistic effect of cocatalyst engineering and radical regulation toward high selectivity in one-step methane conversion - Chuan Yu; Mingli Fu; Keke Tang; Yanjun Li; Lei Liu; Chen Yang; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Comparative study on the changes of triacylglycerol lipolysis products and fatty acid bioaccessibility of four dietary lipids with varying degrees of unsaturation using in vitro digestion model - Yanjun Guo; Zhan Ye; Wei Yang; Rui Xu; Yahui Gao; Yuanfa Liu (Food Bioscience, 2026)

Photo-driven multifunctional membrane evaporator based on Sb2Se3/MoSe2/Ag@PAM for freshwater harvesting and electricity generation - Qiang Zhang; Peiyuan Liu; Zhiwei Yang; Yanjun Liang; Jian Zhang; Lin Wang; Xiao Huang (Chemical Engineering Journal, 2026)

Effects of square-wave excited alternating magnetic fields on calcium carbonate crystallization and their application in scale inhibition - Junwei Zhang; Yandong Liang; Yanjun Yang; Jianguo Wang (Water Research, 2026)

Research on single-phase thermal-hydraulic behavior of the piping system under the influence of mechanical vibration - Xu Chen; Jianxin Shi; Yuanshao Sun; Qingpeng Zeng; Wanze Wu; Xin Zhang; Xichao Liang; Yanjun Li; Jie Yang; Xinrong Wang; Yuanwei Cao (Ocean Engineering, 2026)

Dietary patterns drive sphingolipid metabolic rewiring: Integrative insights from transcriptomics and sphingolipidomics - Shuo Yang; Nan Meng; Xincen Wang; Yanjun Liu; Peixu Cong; Changhu Xue; Jie Xu (Food Bioscience, 2026)

Liposome-encapsulated egg yolk immunoglobulin (IgY) enhances anti-Helicobacter pylori efficacy by alleviating gastric inflammation, oxidative stress, and regulating gut microbiota - Peixin Song; Zhishuo Zhang; Ruyi Zhang; Wei Hu; Shengqi Rao; Yanjun Yang; Cuihua Chang (Food Bioscience, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Dauricine ameliorates intestinal inflammation and oxidative stress in DSS-induced colitis through TLR4/NLRP3/GSDMD-mediated pyroptosis and Nrf2 pathway - Lin Wang; Jingyuan Liu; Jiayi Wang; Yuxin Xie; Yanan Gao; Daili Xu; Jing Li; Jing Dong; Bingyao Li; Yanjun Cao; Yang Li; Jiao He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Combined effects of tropical and mid-high-latitude ISO on the dry- wet sudden transition in the mid-low reaches of the Yangtze River during boreal summer of 2015 - Yuchen Zhao; Shuangyan Yang; Pang-chi Hsu; Yanjun Qi (Climate Dynamics, 2026)

Phosphorus Speciation and Mobility in the Dredged Sediment of an Urban Lake: The Role of Coupled Fe-S-P Dynamics and Microbial Succession - Baoquan Li; Min Zhang; Jicheng Zhong; Jiayu Qin; Haiyuan Cai; Chuanzhe Sun; Fanyan Yang; Yanjun Wu; Shanshan Liu; Hui Yang; Fen Huang (Water Research, 2026)

Decoupling environmental drivers of bioaerosol emissions during food waste degradation - Yanjun Liu; Haiwen Ning; Qiange Tang; Yanfeng Zhang; Zhuowen Chen; Qingfei Li; Jianbing Wang; Zhanhong Yang (Waste Management, 2026)

Electro-trapping uranium(VI) by ternary phosphate-functionalized polymer / molybdenum disulfide / pod shell-derived biochar composite electrode - Dongqing Huang; Yun Wang; Yang Wang; Qidong Ye; Yang Li; Hao Jiang; Yanjun Du; Yan Liu; Dingzhong Yuan; Xianping Luo (Journal of Environmental Management, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Unconventional seasonal variation and mechanisms of sediment phosphorus release in an Urban lake - Baoquan Li; Suisui Zhang; Yanjun Wu; Ying Li; Min Zhang; Chuanzhe Sun; Fanyan Yang; Yuyi Wang; Shanshan Liu; Hui Yang; Fen Huang; Jicheng Zhong (Journal of Environmental Sciences, 2026)

Low-temperature anammox efficiency is governed by matrix-mediated modulation of quorum sensing - Yanjun Zhu; Dong Li; Sen Yang; Sibo Fu; Hongpeng Li; Songyue Li; Huiping Zeng; Jie Zhang (Bioresource Technology, 2026)

The Mesoscopic Mechanisms of Rock Mass Failure under Coupled Blasting and Unloading - Lixiang Xie; Yang Hu; Zhendong Leng; Jianhua Yang; Yanjun Qi; Chao Liu; Wenwei Ma (Rock Mechanics and Rock Engineering, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Engineering Arabidopsis for improved yield and nutritional quality through heterologous expression of maize ZmERF118 gene - Zongjie Wang; Yang Zhao; Xinrui Ma; Yanjun Dong; Manyao Liu; Peng Jiao; Kaisheng Yu; Yimeng Wang; Yiyong Ma; Shuyan Guan (Plant Science, 2026)

Integrative phylogenetics and geography unveil Quaternary diversification and mitochondrial-nuclear discordance in Odorrana schmackeri sensu lato (Anura, Ranidae): Roles of Qinghai-Tibetan uplift, climate oscillations, and asymmetric gene flow - Yanjun Zhu; Zhuo Chen; Yuxiao He; Xinyue Yang; Xiaofei Zhai; Qiuya Wang; Xiaohong Chen; Xiang Ji (Molecular Phylogenetics and Evolution, 2026)

Revealing the impact of short side-chain migration on the digestive kinetics and multiscale structure of ultrasound-treated nano-scale amylopectin endogenous ternary complexes - Bo Li; Mingyang Gao; Chongxing Huang; Xin Yang; Weihong Lu; Yanjun Zhang (Food Hydrocolloids, 2026)

Rainfall partitioning and interception simulation for typical species in the Taihang Mountains, China - Bo Guo; Hui Yang; Chunyu Zhu; Zhibang Yan; Jiansheng Cao; Yanjun Shen (Agricultural and Forest Meteorology, 2026)

Sediment sink-source shifts drive intensified internal phosphorus (P) release during the rainy season in a eutrophic plateau lake - Chaoran Guo; Fu Zhang; Yanjun Wu; Chengfei Tong; Yuyi Wang; Jianxia Cai; Zheng Zhao; Jinliang Liu; Qi Yang; Xiaozhi Gu; Jicheng Zhong; Jizheng Pan (Water Research, 2026)

Electric-carbon market coupling and price transmission mechanism in China: An empirical analysis and development barriers study - Jiajun Wu; Yanjun Shen; Ruitong Yang; Hang Fan; Yunjie Duan (Journal of Cleaner Production, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

The temperature and multi-species evolution during the oxidation of CH3OH/NH3 blends behind reflected shock waves - Dao Zheng; Youquan Yang; Haoyu Tian; Zhimin Peng; Dong He; Yanjun Ding; Yanjun Du (Fuel, 2026)

Corrigendum to “Surface chemistry-driven lipase activation: insights from spectroscopy and molecular simulations”. [Biores. Technol. 436 (2025) 133035] - Jihang Zhang; Siwen Ji; Jinming Zhang; Yihui Luo; Yanjun Chen; Jinglan Wu; Pengpeng Yang; Fengxia Zou; Hanjie Ying; Wei Zhuang (Bioresource Technology, 2026)

Structure-oriented molecular extension strategies unlock C-glycoside insecticides targeting OfChtII and OfHex1 - Yin Ai; Yanjun Zhang; Wei Chen; Xingyue Zhou; Yanhong Dong; Qing Yang; Jianjun Zhang (Pesticide Biochemistry and Physiology, 2026)

Internal phosphorus loading and regulatory mechanism in China's largest urban lake: Implications for eutrophication management - Yuyi Wang; Chuanzhe Sun; Yanjun Wu; Gang Pan; Robert J.G. Mortimer; Fanyan Yang; Shuailong Wen; Suisui Zhang; Lejia Zong; Hezhong Yuan; Jianghua Yu; Jicheng Zhong (Journal of Environmental Management, 2026)

Multidimensional comparative study on the efficacy and mechanisms of radiofrequency and thermal induction inactivation of Aspergillus Niger spore - Yudi Liu; Yanjun Tong; Han Huang; Wei Zhao; Ruijin Yang (Innovative Food Science & Emerging Technologies, 2026)

Enzyme and thermal induced transition of egg white proteins from dense-globular to random coil triggering uniform microparticle formation - Zhishuo Zhang; Yi Wang; Ruyi Zhang; Xuechun Wang; Junhua Li; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang (Food Research International, 2026)

Developing fed-batch strategies to improve high-solid enzymatic hydrolysis of steam-exploded apple pomace - Ruijin Yang; Huanqi Shu; Nuo Xu; Wenhui Zheng; Wei Zhao; Shoushuai Feng; Yanjun Tong (Food Bioscience, 2026)

Research on precursory warning of damage and failure in freeze-thaw sandstone based on acoustic-thermal joint monitoring - Hui Liu; Mengjie Liu; Gengshe Yang; Xinyue Dai; Yanjun Shen; Bo Liang; Xiao Ding; Yali Xu; Runqi Wang (Cold Regions Science and Technology, 2026)

IL-4 in Alzheimer’s Disease—Mechanisms and Therapeutic Potential - Guangya Liu; Weixian Li; Jiangmin Chen; Shuyu Xu; Xinyuan Liu; Zijie Wang; Qihui Yang; Anqi Xie; Yanjun Du (Molecular Neurobiology, 2026)

Fungicide-enhanced differentiation and multidrug resistance of Botrytis cinerea on greenhouse tomato - Bowen Zhang; Zhenren Yang; Chenhui Wang; Yuewei Sun; Yanjun Zhao; Qingchun Huang (Pesticide Biochemistry and Physiology, 2025)

Analysis on the difference of nutrient components of black wolfberry seed grown in different regions - Yichen Liu; Wenyuan Zhang; Yanjun Li; Ruhui Shen; Shuaibei Wang; Xue Wang; Jianjun Deng; Zhenzhen Xu; Haixia Yang (Food Research International, 2025)

High internal-phase pickering emulsions stabilized by mung bean protein–glycyrrhizin complexes for β-carotene delivery - Haoling Yang; Bing Wang; Yanjun Wei; Chenchen Gu; Xianggen Wu (Food Chemistry, 2025)

Structural characterization of water-soluble pectin in NFC orange juice during cloud destabilization - Shiying Yang; Jian Xu; Siying Liu; Yujie Cheng; Fengjiao Cai; Yanjun Zhang; David Julian McClements; Peiyi Shen; Qian Li (Food Chemistry, 2025)

Characterization of Limosilactobacillus fermentum with the efficient conversion of fructose to mannitol and preparation of low-sugar juice - Yanjun Tong; Di Wang; Fang Sun; Rujie Liu; Ruijin Yang (Food Chemistry, 2025)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Se-doped MoS2/CoFe2O4/CNT heterostructures with enhanced electromagnetic wave absorption via structural optimization and phase engineering - Zhigang Wu; Jin Chen; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

The soil organic carbon sequestration potential and formation efficiency of China’s temperate grasslands - Lu Yang; Ping Li; Yuntao Wu; Nairsag Jalaid; Weixing Liu; Xiaoqiang Liu; Ziyang Peng; Junsheng Huang; Xiaoxia Zhao; Lubing Jiang; Zhaoyu Peng; Sen Yang; et al. (Science Bulletin, 2025)

Light-driven release of 6PPD and formation of 6PPD-Q from tire and road wear particles: Mechanisms and cytotoxicity - Danfeng Zhang; Bo Yin; Wen Zhang; Shiyu Wei; Puxing Zhang; Tianyuan Su; Yanjun Liu; Xiwang Tang; Han Wang; Chengfang Yang; Zhuozhi Ouyang; Guining Lu; et al. (Journal of Hazardous Materials, 2025)

Sediment dredging effects on nitrogen and phosphorus release in a stratified reservoir: Implications for internal loading management - Yanjun Wu; Hongwei Wang; Zhu Bao; Yunchuang Li; Xiaokang Hu; Chuanzhe Sun; Fanyan Yang; Baoquan Li; Shanshan Liu; Yuyi Wang; Jicheng Zhong (Journal of Environmental Management, 2025)

Hydrogeochemical mechanism and interconversion processes of groundwater-surface water in the Chan River Basin: A new perspective from hydrochemistry and isotopes - Shuhan Yang; Hui Qian; Panpan Xu; Weijie Zhao; Yixin Liu; Yanjun Shen; Yongqi Zang; Qiming Wang; Zhiming Cao (Journal of Environmental Sciences, 2025)

Correlation between multi-scale structure and log-of-slope digestive kinetics of a novel slowly digestible starch: Self-assembled chempedak seed amylopectin ternary complex - Bo Li; Xin Yang; Yuan Zhao; Chunguang Yao; Chongxing Huang; Shuangfei Wang; Debao Niu; Lehe Tan; Yanjun Zhang; Yutong Zhang (Food Research International, 2025)

Effect of egg yolk component and its enzymatic hydrolysate on the flavor and texture of walnut cake - Tingting Tang; Qing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

Controllable mesoporous wrinkling design realizes interfacial charge engineering in hierarchical MBene/MoS2 heterostructures for enhanced microwave absorption - Yiming Wang; Jin Chen; Bo Li; Meidan Que; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Fe/Fe3O4/FexN@N-doped porous carbon aerogels with superior electromagnetic attenuation performance and multifunctional applications - Yumei Ren; Zhen Qin; Tong Xi; Shuai Yang; Ziran Du; Desheng Feng; Zhongyi Bai; Yanjun Zheng; Xiaoqin Guo; Biao Zhao (Chemical Engineering Journal, 2025)

Chlorination volatilization mechanism for decoupling phosphorus from lead and chromium during sludge incineration - Aijia Zhang; Jing Liu; Yingju Yang; Yanjun Hu; Rundong Li (Chemical Engineering Journal, 2025)

Transparent analysis of compression damage propagation of freeze-thaw rock based on CT-DVC - Hui Liu; Mengjie Liu; Gengshe Yang; Yanjun Shen; Bo Liang; Xiao Ding; Xinyue Dai; Minkai Zhu; Runqi Wang (Cold Regions Science and Technology, 2025)

Surface chemistry-driven lipase activation: insights from spectroscopy and molecular simulations - Jihang Zhang; Siwen Ji; Jinming Zhang; Yihui Luo; Yanjun Chen; Jinglan Wu; Pengpeng Yang; Fengxia Zou; Hanjie Ying; Wei Zhuang (Bioresource Technology, 2025)

Reliable enrichment monitoring and removal of CrO42− and S2− using multivalent W-doped Ag quantum-dot biomimetic nanozyme - Ruhui Shang; Yanjun Han; Huitian Zhi; Xujie Wang; Yingchao Yang; Xiao Zhu; Lei Hu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Arsenic exposure, genetic susceptibility, lifestyle, and glucose-insulin homeostasis impairment: Revealing the association and interaction in a repeated-measures prospective study - Yongfang Zhang; Jiahao Song; Ming Zhang; Gaoyin Xiong; Yanjun Guo; Wei Liu; Linling Yu; Quanhong Liu; Yueru Yang; Shuhui Wan; Qing Liu; Zhiying Huo; et al. (Environmental Research, 2025)

Assessment of Tropical Cyclone Disaster Damage Based on Learnable Inter-City Interaction GNN - Shijin Yuan; Laiyu Yang; Bin Mu; Bo Qin; Yanjun Huang (Journal of Meteorological Research, 2025)

Electric field distribution and selective liberation in magnetite quartzite under high voltage pulse discharge - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang (Minerals Engineering, 2025)

Mechanistic insights into plasmon-mediated charge transfer in Pt@BiOBr/g-C3N4 S-scheme heterojunction for solar-driven water treatment - Jin Chen; Ke Li; Jie Yan; Suqing Qin; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Journal of Water Process Engineering, 2025)

Seasonal freeze-thaw CO2 sink 'midday rest' phenomenon in lakes: A case study of the largest freshwater lake in the Yellow River Basin - Yue Sun; Xiaohong Shi; Ruli Kang; Zhaoxia Yang; Shengnan Zhao; Guohua Li; Yanjun Wang; Jussi Huotari (Journal of Hydrology, 2025)

Transcriptional regulatory factor EpsR mediates adaptation mechanism of extremophile Acidithiobacillus caldus to copper stress environment and performance in bioleaching of low-grade copper ore by enhancing “contact” mechanism - Hongguang Xie; Xingyu Huo; Xiuwen Wang; Zhidong Guo; Yang Yuan; Hailin Yang; Yanjun Tong; Shoushuai Feng (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Mechanism of action of pulsed electric field on lactoferrin: Functional properties, structure and aggregation behavior - Yuhui Ding; Hongfang Cao; Cheng Zhang; Yanjun Tong; Caiyun Wang; Jian He; Wei Zhao; Ruijin Yang (Food Chemistry, 2025)

MOF-based hypocrellin composite nanomaterials as advanced plant-derived photosensitizers for multimodal therapy - Ying'’ao Wu; Yanjun Guo; Kaijie Feng; Miao Li; Hongxue Li; Jiasheng Wu; Pengfei Wang; Rungong Yang; Xiao He; Xiong Yin; Min Li (Chemical Engineering Journal, 2025)

Unlocking the potential of cotton-derived carbon aerogel for uranium extraction from real radioactive wastewater: A path to amidoxime and polyguanidine modification - Yang Wang; Yun Wang; Qi Ren; Zihao Feng; Yang Li; Yanjun Du; Xiaoyan Li; Yan Liu; Dingzhong Yuan; Tu Lan (Chemical Engineering Journal, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Ratio-fluorescence detection of propyl gallate based on MnOOH nanoflakes and β-cyclodextrin modified quantum dots - Bo Peng; Fengxiang Du; Simin Dou; Yuying Yang; Min Zhou; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2025)

Geopolymers prepared from industrial solid waste: Comprehensive properties and application prospects - Wenxing Chen; Huanyi Zhu; Yongmei Li; Fang Liu; Qing Li; Yanjun Mao; Aijiang Yang (Environmental Research, 2025)

Inspiring the potential of graphene oxide aerogel for uranium(VI) electrosorption: A precursor reconfiguration strategy and synergistic integration with polyethyleneimine - Qi Ren; Yun Wang; Yang Wang; Zihao Feng; Yanjun Du; Changfu Wang; Yan Liu; Dingzhong Yuan; Hao Jiang; Yang Li (Desalination, 2025)

Cu@SnO₂/rGO to Cu@Sn/rGO transition: A strategy for tuning plasmon resonance and Schottky junctions in excellent microwave absorbers - Yanjun Jiang; Shuai Lv; Tiantian Li; Xinyu Wang; Pianpian Zhang; Dongdong Lv; Yanan Yang; Xin Wu; Xiaoxiao Huang; Long Xia (Chemical Engineering Journal, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Simultaneously enhance nutrient removal and sludge settleability through hydrocyclone-based technology in a full-scale high-inert containing activated sludge process - Yanjun Shao; Sisi Chen; Xiang Tao; Weilan Yang; Tao Liu; Binzheng Wang; Yan Wang; Shuo Wang; Dongdong Xu; Jianhua Guo; Ji Li (Water Research, 2025)

On the propagation arrest and crossover behavior of pipe bends under external overpressure - Zhenmian Li; Xiangyang Wang; Yanjun Wang; Mingze Huang; Yang Yu; Yaqian Zhao (Ocean Engineering, 2025)

Cysteine and dialysis mediated inhibition of dynamic changes in glycosylated egg white protein during storage - Lulu Guo; Wanqiu Zhang; Fan Zhang; Shende Hu; Qianwen Zhao; Cuihua Chang; Junhua Li; Zijian Huang; Luping Gu; Yanjun Yang; Yujie Su (Food Chemistry, 2025)

GPS flex power detection leveraging XGBoost machine learning based on LEO satellites - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Wanqiang Yao; Qin Li (GPS Solutions, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

Signal-on aptasensors on paper-based platform: Application of multilayer MXene nanoquencher and stabilized luminescent carbon dots - Jincai Yang; Mingzhu Liu; Jin Wu; Tianyi Ma; Yanxuan Li; Yue Zhang; Jingran Sun; Xiaoli Li; Yanjun Fang; Yonghui Wang; Lingchao Cai; Yuan Peng; et al. (Journal of Hazardous Materials, 2025)

Decoding the effect of antibiotics on biofilm formation in biofilters - Sen Yang; Dong Li; Sibo Fu; Jifang Zheng; Yanjun Zhu; Hongpeng Li; Huiping Zeng; Jie Zhang (Journal of Environmental Management, 2025)

Organic substitution enhances soil quality, soil microbial community stability, foxtail millet productivity, and grain quality in North China - Mengen Nie; Xue Gao; Lijie Zhao; Genlan Han; Yanyan Duan; Ruihua Han; Shuqi Dong; Yongling Li; Huiling Du; Xiangyang Yuan; Yanjun Yang (Journal of Environmental Management, 2025)

Disruption of agr quorum sensing for enhancing biofilm formation and butanol production in Clostridium acetobutylicum - Tianpeng Chen; Yuqi Wang; Yanjun Chen; Pengpeng Yang; Wenjun Sun; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Effect of adding different egg yolk oil on the flavor and physicochemical properties of mayonnaise - Xuejing Gao; Tingting Tang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Production of glycerylphosphorylcholine-enriched defatted egg yolk powder through integrated enzymatic and supercritical CO2 processing - Wen Yu; Luping Gu; Cuihua Chang; Yujie Su; Yi Wang; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Single-B-cell cloning and recombinant antibodies generation to analyze the antigenicity of porcine reproductive and respiratory syndrome virus nonstructural protein 12 - Hongyong Duan; Chaozhi Tang; Song Han; Nan Yang; Shumao Wang; Fei Gao; Yanjun Zhou; Guangzhi Tong; Kuan Zhao; Liwei Li (Veterinary Microbiology, 2025)

Tectonic setting, paleoenvironment and REE source of the Lower Cambrian phosphorites, Yangtze Block (South China) - Chuan Guo; Yong Fu; Peng Xia; Zhen Yang; Yanjun Li; Zhongfei Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluation of the Association Between Coffee Consumption, Including Type (Instant, Ground), and Addition of Milk or Sweeteners and New-Onset Hypertension and Potential Modifiers - Mengyi Liu; Yanjun Zhang; Ziliang Ye; Sisi Yang; Yuanyuan Zhang; Panpan He; Chun Zhou; Xianhui Qin (Journal of the Academy of Nutrition and Dietetics, 2025)

Insight into perfluorooctanoic acid-induced impairment of mouse embryo implantation via single-cell RNA-seq - Xiaoqiang Sheng; Yanjun Yang; Jiao Tian; Zhe Zhang; Lijun Ding; Junzhao Zhao (Journal of Hazardous Materials, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

Exploring the interaction between quorum sensing and sludge physical properties in Anammox systems - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Songyue Li; Yuliang Zhu; Huiping Zeng; Jie Zhang (Bioresource Technology, 2025)

Mechanism of rainfall-induced loess landslides revealed by multi-source data - HongYu Liu; YanJun Li; MingZhou Bai; Xu Gao; Ling Yang; ZiLun Zhang; MingHui Zuo; Qain Liu (Natural Hazards, 2025)

Altered functional connectivity within and between resting-state networks in ulcerative colitis - Yanjun Ren; Kaizhong Xue; Huijuan Xu; Lijie Hao; Quchuan Zhao; Tianyu Chi; Hongwei Yang; Xiaojing Zhao; Defeng Tian; Huihong Zhai; Jie Lu (Brain Imaging and Behavior, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Differentiated electromagnetic wave absorption enabled by load modulation of cross-dimensional SiC nanostructures - Baolong Guo; Yanjun Jiang; Yanxin Zhang; Yi Wang; Jingyu Wang; Anqi Lun; Pianpian Zhang; Dongdong Lv; Xinyu Wang; Yanan Yang; Long Xia (Chemical Engineering Journal, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Insights into relationship of oxidative potential of particles in the atmosphere and entering the human respiratory system with particle size, composition and source: A case study in a coastal area in Northern China - Ruiyu Li; Caiqing Yan; Yingze Tian; Yan Wu; Ruizhi Zhou; Qingpeng Meng; Li Fang; Yang Yue; Yanjun Yang; Haibiao Chen; Lingxiao Yang; Wei Jiang (Journal of Hazardous Materials, 2025)

Metal-loaded biochar catalyzed pyrolysis of wood-plastic composite waste into gasoline and aromatic hydrocarbons - Deshi Yang; Jianpeng Huang; Zhipeng Hu; Wei Liu; Fengqiang Wang; Zhijun Zhang; Yanjun Xie; Qingwen Wang (Fuel, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Low-carbon bioconversion of corn stover through whole process design - Jingjiu Mu; Lei Wang; Fan Wang; Weihong Liao; Hailing Dai; Yajing Yang; Yanjun Jiang; Lijuan Liu; Xiao Men; Haibo Zhang (Chemical Engineering Journal, 2025)

3D printing food flow in different extruders based on crazy and adaptive salp swarm algorithm-deep extreme learning machine improved-lattice Boltzmann method - Weiwei Wu; Minheng Gu; Xin Liu; Zhongyi Shan; Shuang Ding; Yanjun Zhang; Wenhan Yang (Journal of Food Engineering, 2025)

Extraction of Au(I) from a thiosulfate leach liquor using guanidinium ionic liquid (C8)2dmg+Br− in 20 % (v/v) n-octanol/n-heptane diluent and stripping with aqueous NaCl - Lingli Liu; Guiping Zhu; Chen He; Yanjun Chen; Yewei Qiu; Shixiong Wang; Conghai Zhang; Xiangjun Yang (Hydrometallurgy, 2025)

The catalytic mechanism for H2 production on MgO-CaO materials through the water gas shift reaction: A DFT study - Pengfei Zhao; Yanjun Wu; Chuanjiang Yang; Ke Wang; Peisheng Li; Edward J. Anthony; Cheng Fang (Gas Science and Engineering, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Association of prebiotic/probiotic intake with MASLD: evidence from NHANES and randomized controlled trials in the context of prediction, prevention, and a personalized medicine framework - Senlin Wang; Ruimin Zhang; Peisen Guo; Huawu Yang; Yanjun Liu; Hongmei Zhu (EPMA Journal, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

Settlement prediction of a high embankment based on non-linear regression and neural network algorithm - Enhui Yang; Kai Wang; Jinhong He; Kaiwen Liu; Junxin Wang; Haopeng Zhang; Yanjun Qiu (Transportation Geotechnics, 2025)

Uncovering a cryptic Streptococcus suis endemic post-outbreak: Evidence of host switching to humans - Shuirong Zhu; Shengkai Li; Beibei Wu; Zhangnv Yang; Yuwen Zhang; Jiancai Chen; Yanjun Zhang; Lei Fang (Science of The Total Environment, 2025)

Mechanisms by which Ganglioside GM1, a specific type of glycosphingolipid, ameliorates BMAA-induced neurotoxicity in early-life stage of zebrafish embryos - Yanjun Liu; Yuhe Zhu; Xiaoxu Wang; Yiyang Li; Shuaiqi Yang; Hongyan Li; Bo Dong; Zhigao Wang; Yu Song; Jie Xu; Changhu Xue (Food Research International, 2025)

Damage evolution characteristics of freeze–thaw rock combined with CT image and deep learning technology - Hui Liu; Xinyue Dai; Gengshe Yang; Yanjun Shen; Pengzhi Pan; Jiami Xi; Borong Li; Bo Liang; Yao Wei; Huiqi Huang (Bulletin of Engineering Geology and the Environment, 2025)

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

L1-Tree: A novel algorithm for constructing 3D tree models and estimating branch architectural traits using terrestrial laser scanning data - Yuhao Feng; Yanjun Su; Jiatong Wang; Jiabo Yan; Xiaotian Qi; Eduardo Eiji Maeda; Matheus Henrique Nunes; Xiaoxia Zhao; Xiaoqiang Liu; Xiaoyong Wu; Chen Yang; Jiamin Pan; et al. (Remote Sensing of Environment, 2024)

Adaptation mechanisms and efficiency of anammox bacterial aggregates in various reactor systems during the start-up period - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Jifang Zheng; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Extraction of egg yolk lipids via salt-induced synergistic heat treatment: Fabrication, characterization and flavor analysis - Xuejing Gao; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Enhancing acid resistance of Escherichia coli based on directed morphology evolutionary of key transcription factor bolA - Zongling Chen; Xingyu Huo; Jiali Wan; Jinming Che; Meiyi Deng; Yingnan Bao; Hailin Yang; Yanjun Tong; Shoushuai Feng (Food Bioscience, 2024)

Multi-scale structural and In vitro digestion properties of amino acids-tiger nut starch complexes and applications in noodles - Shiqi Zhang; Yiming Jiang; Zihan Gao; Juncai Leng; Tingyi Zhou; Han Liu; Chenlu Zhu; Yanjun Tong; Wenbin Zhang; Ruijin Yang (Food Bioscience, 2024)

High-pressure processing for pickled crabs: Safety, quality and flavor assessment and correlation analysis of spoilage indicators - Han Huang; Yudi Liu; Yanjun Tong; Wei Zhao; Xiaomei Lyu; Ruijin Yang (Food Bioscience, 2024)

Effects of non-covalently bound polyphenols/vitamins on the structure and functional characteristics of egg yolk powder - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Towards a high-rate operation of contact stabilization process: A microscopic view of carbon capture properties - Sibo Fu; Dong Li; Kunming Fu; Xiaohang Zhang; Yanjun Zhu; Sen Yang; Huiping Zeng; Jie Zhang (Environmental Research, 2024)

Intermetallic synergy in trimetallic alloy for highly-efficient hydrogen production from ammonia decomposition - Yanjun Sun; Weihao Zeng; Yangju Yang; Qiming Wu; Chun Zou (Chemical Engineering Journal, 2024)

Separation of Gold(I) from cyanide-containing wastewater by functional polymer inclusion membrane containing guanidinium ionic liquid - Guiping Zhu; Yanjun Chen; Yewei Qiu; Yuan Zhang; Feng Li; Fengzhi Jiang; Xiangjun Yang; Shixiong Wang (Chemical Engineering Journal, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

High-performance cellulose/thermoplastic polyurethane composites enabled by interaction-modulated cellulose regeneration - Yuhui Ci; Dong Lv; Xiangjian Yang; Haishun Du; Yanjun Tang (Carbohydrate Polymers, 2024)

Tracing groundwater-surface water sources and transformation processes in the Ba River Basin through dual isotopes and water chemistry - Weijie Zhao; Hui Qian; Panpan Xu; Shuhan Yang; Yixin Liu; Yanjun Shen; Yongqi Zang; Qiming Wang; Zhiming Cao (Applied Geochemistry, 2024)

Hydroxylamine-induced activation of permanganate for enhanced oxidation of sulfamethoxazole: Mechanism and products - Xiaohui Lu; Yanjun Li; Hongyu Zhou; Siyu Li; Wei Wei; Guochun Lv; Gang Yang; Shihuai Deng; Bo Lai; Jiali Peng (Science of The Total Environment, 2024)

Towards a high-rate operation of contact stabilization process: Challenges of flocculation and floc stability - Sibo Fu; Dong Li; Kunming Fu; Yanjun Zhu; Sen Yang; Xiaohang Zhang; Jie Zhang (Journal of Environmental Management, 2024)

Relationship between environmental evolution and human activities in the northeastern Qinghai-Xizang Plateau throughout the past millennium and its implications for the onset of the Anthropocene - Yang Pu; Xueqiong Wei; Jianbao Liu; Ke Zhang; Beibei Li; Zhudeng Wei; Mengmeng Zhang; Tong He; Yanjun Wang; Xiaohua Shao (Science China Earth Sciences, 2024)
In current research on the Anthropocene, assessing the impact of human activities via stratigraphic records of sediments and demarcating the Anthropocene epoch globally are critical scientific issues that urgently need to be addressed. The northeastern Qinghai-Xizang Plateau (QXP), where humans first settled permanently in large numbers in the QXP, has varying sedimentary environments that are extremely sensitive to human activities. In contrast to other regions of the QXP, the northeastern sector boasts a richer array of climatic and environmental reconstruction sequences. This distinctive feature renders it an exemplary locale for investigating the stratigraphic boundary of the Anthropocene. Through in-depth analysis and integration of existing paleoclimate and paleoenvironment sequences in the northeastern QXP, we draw the following conclusions: (1) Throughout the past millennium, the impact of human activities on the environment of the northeastern QXP has become increasingly significant, especially in the past 200–300 years, gradually overshadowing climatic factors. (2) Since AD 1950, multiple physicochemical indicators related to human activities in the northeastern QXP have shown exponential growth, forming a distinct peak within the past millennium and clearly depicting the global “Great Acceleration” phenomenon and its development process. (3) Intensified human activities have driven swift environmental shifts and “decoupled” the interplay between climatic variations and the ecological environment, propelling the northeastern QXP into the “Early Anthropocene” from the “Late Holocene”. On the basis of the above findings, we construct a model suitable for identifying the stratigraphic boundary of the Anthropocene in the northeastern QXP and note that since the ecological environment in the northeastern QXP has entered the “Early Anthropocene”, the climate signals of certain physicochemical indicators in sediments are gradually becoming weaker, whereas the signals of human activities are becoming stronger.

Study on the source identification and migration and transformation characteristics of heavy metal pollution in sediments of Chaohu Lake Tongyang River Basin - Zhenyu He; Yanjun Li; Bo Kang; Rui Li; Kun Chen; Jie Yang; Yuezan Tao (Environmental Monitoring and Assessment, 2024)

Development of egg yolk lipoprotein hydrolysate for nano-delivery of curcumin: Structure-function relationship - Lili Jiang; Yanjun Yang; Yujie Su; Cuihua Chang; Luping Gu; Chunfang Liu; Junhua Li (Innovative Food Science & Emerging Technologies, 2024)

Hydrodesulfurization kinetic modeling of mixed Feedstocks: An approach using structure-oriented lumping for complex diesel oils - Mengfei Wang; Heping Yang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Advancing bioethanol production with a new kinetic model based on structure-oriented lumping for cellulose conversion - Heping Yang; Mengfei Wang; Xiaowei Bai; Zhenghua Dai; Yunpeng Zhao; Yanjun Hu; Jian Li (Fuel, 2024)

Circulating metabolomics revealed novel associations between multiple ambient air pollutants exposure and chronic obstructive pulmonary disease incidence: Evidence from a prospective cohort study - Liangle Yang; Yanjun Guo; Yuxin Yao; Yujia Xie; Shiyu Yang; Bingxin Shang; Xiaojie You; Haoxiang Liu; Jixuan Ma (Environmental Pollution, 2024)

Anthropogenic activities have accelerated the restoration of carbon sequestration services in the upper Yellow River - Junyi Yang; Junsheng Li; Xiao Guan; Yanjun Chen; Zemin Zhang; Wenjie Li (Ecological Engineering, 2024)

Timescale dependent homogeneous assembly of lipid-polymer hybrid nanoparticles in laminar mixing for enhanced lung cancer treatment - ShiXin Li; Bing Yang; Liang Ye; ShuQi Hu; BenHong Li; Yanjun Yang; XiaoBin Jia; Liang Feng; ZhiWei Xiong (Chemical Engineering Journal, 2024)

The role of aquaporins in osmotic cell lysis induced by Bacillus thuringiensis Cry1Ac toxin in Helicoverpa armigera - Yanjun Cai; Bofeng Hou; Jeffrey A. Fabrick; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2024)

Parameter analysis and dual-objective optimization of the hydraulic power take-off system of a floating wind-wave hybrid system - Shuting Huang; Jun Wang; Mingyu Yang; Ge Dong; Yuanzhi Wang; Yanjun Liu (Ocean Engineering, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Generation and persistency of combustion-derived environmentally persistent free radicals from phenolic compounds over a Fe2O3/SiO2 surface - Yanjun Hu; Guohao Yang; Nan Zhou; Long Jiao; Lei Wang; Jianhua Yan (Chemosphere, 2024)

Production of cleavage-resistant phytase transgenic pigs by handmade cloning - Mingyuan Zhang; Jun Zhang; Haowen Yang; Shijin Chen; Xiaoliang Chen; Yuemeng Huang; Baojian Chen; Yanjun Wu; Qinyang Jiang; Yafen Guo; Yingming Wei; Xiukun Lin; et al. (Theriogenology, 2024)

New insights of selective rupture of synthetic sample under high voltage pulse discharge: A numerical simulation of electric field distribution - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang; Jianming Gao (Minerals Engineering, 2024)

Dual pathways of aragonite-to-calcite transformation in stalagmites: Implications for paleoclimate reconstructions - Rui Zhang; Haiwei Zhang; Christoph Spötl; Hai Cheng; Yanjun Cai; Carlos Pérez-Mejías; Xiyu Dong; Lijuan Sha; Youwei Li; Liangcheng Tan; Jingjie Zang; Xunlin Yang; et al. (Geochimica et Cosmochimica Acta, 2024)

Comprehensive analysis of the metabolome and the whole genome transcriptome to reveal the regulatory mechanism the flavor of Phallus rubrovolvatus - Jian Wang; Haoyuan Tian; Yanjun Xu; Xingcan Peng; Chao Zhang; Meilin Lu; Zhenghua Lu; Shunyi Xu; Tingchi Wen; Chenglong Yang (Food Bioscience, 2024)

Differential effects of egg consumption on fecal lipid metabolism: Insights from C57BL/6J mice under chow diet and high-fat diet - Fan Zhang; Tian Yang; Junhua Li; Luping Gu; Cuihua Chang; Li Yang; Zijian Huang; Yujie Su; Yanjun Yang (Food Bioscience, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Heteroaggregation kinetics of nanoplastics and soot nanoparticles in aquatic environments - Dehua Zeng; Chen Yang; Ziqing Huang; Yanjun Liu; Sijia Liu; Zhiyu Zhang; Weilin Huang; Zhi Dang; Chengyu Chen (Journal of Hazardous Materials, 2024)

National-scale Geochemical Survey: Distribution of chemical elements in stream sediment of South and Central Asia - Jun Hong; Guanglu Meng; Jing Zhang; Jifei Cao; Bin Wang; Yanjun Luo; Bo Yang; Xueqi Zhang; Domenico Cicchella (Journal of Geochemical Exploration, 2024)

Hydrothermally Ce modified HZSM-5 zeolite enhancing its strong acidity and Brønsted/Lewis acid ratio: Stably boosting ethylene/propylene ratio for cracking n-heptane - Qi Liu; Zhengkang Yang; Zikang Chen; Peng Xiao; Yafen Ge; Yu Piao; Yanjun Gong (Fuel, 2024)

Four-in-one multifunctional self-driven photoelectrocatalytic system for water purification: Organics degradation, U(VI) reduction, electricity generation and disinfection against bacteria - Sixuan Cai; Yanjun Wen; Qingyan Zhang; Qingming Zeng; Qingqing Yang; Beibei Gao; Guolong Tang; Qingyi Zeng (Science of The Total Environment, 2024)

Exploration of individual colorectal cancer cell responses to H2O2 eustress using hopping probe scanning ion conductance microscopy - Dong Wang; Emily Woodcock; Xi Yang; Hiromi Nishikawa; Elena V. Sviderskaya; Masanobu Oshima; Christopher Edwards; Yanjun Zhang; Yuri Korchev (Science Bulletin, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

SPR effect and internal electric field in Pt@BiOBr/(001)-TiO2 S-scheme heterojunction for visible-light-driven photocatalytic degradation of tetracycline hydrochloride and dyes - Jie Yan; Jin Chen; Xiaofeng Yang; Yueying Wang; Xinle Wang; Jianye Shi; Jing Zhang; Yuzhao Ma; Yanjun Li (Journal of Water Process Engineering, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Riboflavin alleviates the occurrence of anthracnose caused by Colletotrichum gloeosporioides in postharvest mango and the possible mechanisms involved - Mingtao Zhu; Zhuanying Yang; Neng Wang; Liangjie Chen; Yanjun Xiao; Lijun Yu; Chunyan Long; Xinjie Yang; Jun Yu (Food Bioscience, 2024)

Investigation into the impact of enzyme treatment on the structural characteristics of egg yolk protein and its correlation with flavor constituents - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of a novel dual-enzyme modification method for the functionality improvement of egg yolk powder - Huan Rui; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Systems engineering of Escherichia coli for high-level l-alanine production - Yupeng Nie; Mingjing Yao; Guozheng Jiang; Yi Yang; Shenbiao Wang; Hui Xu; Jiayuan Liang; Xuebing Ren; Yanjun Tian (Food Bioscience, 2024)

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)

Soil pH is the Primary Factor Driving the Transformation of Plant Cuticular Wax in Saline Soils - Jianfeng Yang; Tianyu Wang; Yingpeng Sun; Yu Ni; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2024)

Associations of polychlorinated biphenyls exposure, lifestyle, and genetic susceptibility with dyslipidemias: Evidence from a general Chinese population - Yuxin Yao; Min Zhou; Qiyou Tan; Ruyi Liang; Yanjun Guo; Dongming Wang; Bin Wang; Yujia Xie; Haoyu Yin; Shiyu Yang; Bingxin Shang; Xiaojie You; et al. (Journal of Hazardous Materials, 2024)

Consumers' willingness to pay for carbon-labeled agricultural products and its effect on greenhouse gas emissions: Evidence from beef products in urban China - Xuan Chen; Shihang Zhen; Shaoting Li; Jieyu Yang; Yanjun Ren (Environmental Impact Assessment Review, 2024)

Cost-effective and high-performance biguanide-incorporated ionic porous organic polymer for selective recovery of Pd(II) and Pt(IV) from metallurgical wastewater - Jiaxing Xiong; Yuan Zhang; Yanjun Chen; Zhicun Zhou; Jing Zhang; Shixiong Wang; Xiangjun Yang (Chemical Engineering Journal, 2024)

Interannual variability of mid-high-latitude intraseasonal oscillation intensity at the southern hemisphere during austral summer - Shuangyan Yang; Qinghan Xu; Zhiwei Zhu; Yanjun Qi (Climate Dynamics, 2024)

Mineral transformation, element transport and hydrological impact in weathering at the Bingling Temple Grottoes: Implications for weathering in alkaline environments in NW China - Ruxue Liao; Wenwu Chen; Peiran Liu; Li Wang; Qian Xia; Xiaoyan Yang; Yanjun He; Qinglin Guo (CATENA, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Decoding PFAS contamination via Raman spectroscopy: A combined DFT and machine learning investigation - Yangxiu Chen; Yanjun Yang; Jiaheng Cui; Hong Zhang; Yiping Zhao (Journal of Hazardous Materials, 2024)

Fabrication of phosphatidylcholine-EGCG nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in a Caco-2 monolayer model - Mengya Zhang; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Chemistry, 2024)

In situ growth of Zr-based metal-organic frameworks on cellulose sponges for Hg2+ and methylene blue removal - Yanxiao Yang; Yunfeng Guo; Zhe Qiu; Weihua Gong; Yonggui Wang; Yanjun Xie; Zefang Xiao (Carbohydrate Polymers, 2024)

Influence of the mid-high-latitude Eurasian ISO on PM2.5 concentration anomaly in North China during boreal winter - Shuangyan Yang; Yashu Liu; Zhiwei Zhu; Yanjun Qi (Climate Dynamics, 2024)

The cuticular wax on sorghum straw influenced soil microbial diversity and straw degradation in soil - Daixiang Xu; Cai Qi; Jianfeng Yang; Yu Ni; Yanjun Guo (Applied Soil Ecology, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Aluminum speciation in polymerized aluminum chloride: Roles and chloride ion migration in sludge dewatering - Yanjun Zhu; Hongyun Li; Peng Yang; Dong Li; Ziyan Wang; Yunpeng Qi; Jie Zhang (Journal of Environmental Chemical Engineering, 2024)

Catalytic conversion of lignin into monoaromatic hydrocarbons over a Ni/Al hydrotalcite-derived catalyst - Deshi Yang; Jianpeng Huang; Zhipeng Hu; Yuanyuan Miao; Fengqiang Wang; Zhijun Zhang; Yanjun Xie; Shouxin Liu; Qingwen Wang; Charles U. Pittman (Fuel, 2024)

Effects of cholesterol removal treatment on the flavor and physicochemical properties of hot gel egg yolk - Tingting Tang; Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Differences in the gelation, digestibility and release of antioxidant peptides of egg white/yolk in boiled eggs - Min Zhu; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

Communication Management and Data Compression Algorithm Design of BeiDou Transparent Transmission Terminal for Argo Buoy - Hongyu Li; Yanjun Fan; Yicheng Wen; Yanchao Zou; Qingfeng Ma; Shaobo Yang (Journal of Marine Science and Engineering, 2024)
The Argo buoy detects marine environmental data by making profile movements in the ocean and transmits the profile detection data to the shore base through the communication terminal. However, due to the large volume of data collected from profile detections and the continuous operation of the terminal, the remote communication of buoys is characterized by lengthy communication times and significant power consumption. A low-power Beidou transparent transmission terminal is designed to solve these problems in this paper. The terminal performs low-power operation management and power management for terminal remote communication. After the end of a communication process, the microcontroller turns the Beidou module power off and enters STOP mode. Before the next communication process begins, the serial port wakes up the microcontroller, which powers up the Beidou module. Before the remote communication, the microcontroller compacts the profile detection data collected by the buoy to reduce the quantity of remote communication data. In this paper, a variety of data compression methods are used to compare the compression rate, and the best compression method is selected according to the format characteristics of the data. The results show that the Beidou transparent transmission terminal of the Argo buoy can realize low power consumption for remote communication in ocean exploration. The terminal reduces power consumption by 77.282% per communication, and the average number of remote communications for each profile detection data are reduced by 55 times. The low-power Beidou transparent transmission terminal improves the battery life and is conducive to the long-term operation of the buoy.

A real-time fluorogenic recombinase polymerase amplification microfluidic chip (on-chip RPA) for multiple detection of pathogenic microorganisms of penaeid shrimp - Qiang Li; Lijun Duan; Dongsheng Jin; Yuxin Chen; Yirong Lou; Qianjin Zhou; Zhongjie Xu; Fangjie Chen; Hongxian Chen; Guizong Xu; Maocang Yan; Guanjun Yang; et al. (Aquaculture, 2024)

Ultra-high adsorption capacity and selectivity of photo-enhanced sulfur-rich M2S3 (M Bi and Sb) for gold recovery from electronic wastewater - Lingling Zhao; Qiaoshu Zhou; Yun Yang; Yuan Zhang; Yewei Qiu; Yanjun Chen; Xian Jin; Xiangjun Yang; Shixiong Wang (Journal of Water Process Engineering, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

The Numerical Investigation of Solid–Liquid Two-Phase Flow Characteristics Inside and Outside a Newly Designed 3D Sediment Trap - Zhihao Xu; Zihang Fei; Yusen Zhu; Cheng Wang; Xiuqing Yang; Lei Guo; Gang Xue; Yanjun Liu (Journal of Marine Science and Engineering, 2023)
Sediment transport serves as a link for material exchange between land and sea. Using sediment traps, we can observe the capture and transport processes of sediments. Based on the sediment particle size distribution characteristics in Jiaozhou Bay, this paper analyzes the influence of a newly designed 3D sediment trap on the water–sand two-phase flow process inside and outside a trap device during its operation. Meanwhile, under a certain concentration condition, a numerical formula model is researched and proposed to evaluate the impact of the device’s structure, the environmental flow speed, and the particle size on particle capture efficiency. This model is based on the CFD-DPM coupling in Fluent 2021R1 software, and the particle filtration process is solved using a combination of porous media and UDF functions. Finally, by analyzing the distribution of sediment movement in the fluid domain, two concepts, namely the percentage of particles entering the tube and the effective capture rate, are proposed. Suggestions for optimizing the structure of the trap are put forward to achieve optimal capture effects.

Rapid start-up of the biofilter for simultaneous manganese and ammonia removal at low temperature: Effects of phosphate and copper - Jifang Zheng; Dong Li; Huiping Zeng; Sen Yang; Yanjun Zhu; Jie Zhang (Journal of Cleaner Production, 2023)

Critical impact of pyrolysis temperatures on biochars for peroxymonosulfate activation: Structural characteristics, degradation performance and mechanism - Suyun Pei; Yanjun Zhao; Wenhui Li; Chen Qu; Yifan Ren; Yue Yang; Jiemin Liu; Chuandong Wu (Chemical Engineering Journal, 2023)

Experimental studies on the effects of thermal damage in coal-derived mudstones caused by high temperatures - Yanjun Shen; Ziyi Li; Cheng Peng; Bohan Yang; Tianchi Ma (Acta Geodaetica et Geophysica, 2023)

Positive association between ambient air pollutants and incident kidney stones - Xiaoqin Gan; Yanjun Zhang; Panpan He; Ziliang Ye; Chun Zhou; Mengyi Liu; Sisi Yang; Yuanyuan Zhang; Xianhui Qin (Environmental Science and Pollution Research, 2023)

A similarity distance-based space-time random forest model for estimating PM2.5 concentrations over China - Shikang Guan; Xiaotong Zhang; Wenbo Zhao; Yanjun Duan; Shuyue Yang; Yunjun Yao; Kun Jia (Atmospheric Environment, 2023)

Application of eDNA metabarcoding for monitoring the fish diversity of the Jiangjin to Fuling section of the upper reaches of the Yangtze River - Ruli Cheng; Yang Luo; Qinghua Li; Yufeng Zhang; Zhihao Liu; Qiliang Chen; Yingwen Li; Yanjun Shen (Hydrobiologia, 2023)

Ammonia emission characteristics and ammonia injection control from stationary source in flue gas denitrification system - Zhiping Wang; Chengyi Sun; Aijun Shi; Jing Yan; Lei Nie; Lei Chen; Peili Zhou; Yanjun Ding; Yong Yang; Xianglong Jing (Journal of Cleaner Production, 2023)

Fabrication of egg white protein/phosphatidylcholine-EGCG co-assembled nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in Caco-2 cultures - Mengya Zhang; Xuejing Gao; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Hydrocolloids, 2023)

Importation of a novel Indian Ocean lineage carrying E1-K211E and E2-V264A of Chikungunya Virus in Zhejiang Province, China, in 2019 - Lingxuan Su; Xiuyu Lou; Hao Yan; Zhangnv Yang; Haiyan Mao; Wenwu Yao; Yi Sun; Junhang Pan; Yanjun Zhang (Virus Genes, 2023)
The chikungunya virus (CHIKV) is widespread. In Zhejiang province, China, CHIKV infection is often associated with travelers from tropical and subtropical countries. In the present study, three CHIKV isolates from serum samples of travelers in Zhejiang province in 2019 were sequenced, and phylogenetically analyzed to study their molecular characteristics. Sequence analysis showed that the non-structural protein and the structural protein had 37 and 28 amino acid mutations, respectively; no mutation site was found at the E1-A226 residue, which could increase the adaptability of CHIKV to Aedes albopictus . All three samples carried two mutations, namely, E1-K211E and E2-V264A, which were introduced to Bangladesh around late 2015 and Thailand in early 2017. Phylogenetic analysis revealed that these three CHIKVs were Indian Ocean lineage of the East Africa/Central/South Africa genotype (ECSA) and that the MF773566 strain from Bangladesh (Australia/Bangladesh 2017) had the closest evolutionary relationship. The three CHICKs imported into Zhejiang province in 2019 belonged to the ECSA genotype and had multiple amino acid variation sites. The variation in the three samples provides a certain reference for the subsequent research on CHIKV evolution.

Uncovering the virome and its interaction with antibiotic resistome during compost fertilization - Qingxia Zhang; Lei Zhou; Yilong Zhao; Shuhong Gao; Yanjun Yang; Qingyun Chen; Wenhui Li; Qi Qi; Qiang Dong; Jiesi Lei; Xue Guo; Qun Gao; et al. (Journal of Hazardous Materials, 2023)

Gene-environment interaction in long-term effects of polychlorinated biphenyls exposure on glucose homeostasis and type 2 diabetes: The modifying effects of genetic risk and lifestyle - Qiyou Tan; Shijie Yang; Bin Wang; Mengyi Wang; Linling Yu; Ruyi Liang; Wei Liu; Jiahao Song; Yanjun Guo; Min Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Study on detection method of microplastics in farmland soil based on hyperspectral imaging technology - Lijia Xu; Yanjun Chen; Ao Feng; Xiaoshi Shi; Yanqi Feng; Yuping Yang; Yuchao Wang; Zhijun Wu; Zhiyong Zou; Wei Ma; Yong He; Ning Yang; et al. (Environmental Research, 2023)

A novel vertical immobilized photocatalytic membrane reactor based on Bi2WO6-g-C3N4/PVDF for enhanced removal of atrazine, anti-fouling performance and long-term stability - Chunyan Yang; Zhihao Zhang; Peng Wang; Peng Xu; Tianyao Shen; Yanjun Xin; Guangshan Zhang (Chemical Engineering Journal, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

Rainfall intensity affects the recharge mechanisms of groundwater in a headwater basin of the North China plain - Wenbo Zheng; Shiqin Wang; Kangda Tan; Yanjun Shen; Lihu Yang (Applied Geochemistry, 2023)

Anticipating on potential electron acceptors for Anammox - Yanjun Zhu; Dong Li; Saiyue Qi; Sen Yang; Jie Zhang; Wenqiang Wang; Shuai Li (Chemical Engineering Journal, 2023)

Insights into the catalytic mechanism of a type I sulfide quinone oxidoreductase (SQR) from Acidithiobacillus caldus - Xiaoyang Lu; Linghui Zhao; Yanjun Tong; Hailin Yang; Shoushuai Feng (Systems Microbiology and Biomanufacturing, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Enhancement of acid tolerance of Escherichia coli by introduction of molecule chaperone CbpA from extremophile - Zhenming Jiang; Jie Lu; Yanjun Tong; Hailin Yang; Shoushuai Feng (World Journal of Microbiology and Biotechnology, 2023)

Functional characterization of three TERMINAL FLOWER 1-like genes from Platanus acerifolia - Sisi Zhang; Qin Zhou; Xingyu Yang; Jianqiang Wang; Jie Jiang; Miaomiao Sun; Yanjun Liu; Chaoren Nie; Manzhu Bao; Guofeng Liu (Plant Cell Reports, 2023)

Efficiency and mechanism on photocatalytic degradation of fluoranthene in soil by Z-scheme g-C3N4/α-Fe2O3 photocatalyst under simulated sunlight - Guoliang Yang; Yan Jiang; Bingjie Yin; Guocheng Liu; Dong Ma; Guangshan Zhang; Guodong Zhang; Yanjun Xin; Qinghua Chen (Environmental Science and Pollution Research, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Influence of selected gums on the foaming properties of egg white powders: Kinetics of foam formation and baking performance - Junhua Li; Jinjing Sun; Cuihua Chang; Luping Gu; Yujie Su; Jiali Zhai; Yanjun Yang (Food Hydrocolloids, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Environmental-friendly and effectively regenerate anode material of spent lithium-ion batteries into high-performance P-doped graphite - Xiuying Yang; Honggang Zhen; Haozhou Liu; Chaojiu Chen; Yanjun Zhong; Xiushan Yang; Xinlong Wang; Lin Yang (Waste Management, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

Relations of residential green and blue spaces with new-onset chronic kidney disease - Mengyi Liu; Ziliang Ye; Panpan He; Sisi Yang; Yanjun Zhang; Chun Zhou; Yuanyuan Zhang; Xiaoqin Gan; Xianhui Qin (Science of The Total Environment, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Sugar alcohols as cryoprotectants of egg yolk: Inhibiting crystals and interactions - Haosheng Zhu; Junhua Li; Yujie Su; Luping Gu; Cuihua Chang; Yanjun Yang (Journal of Food Engineering, 2023)

Essential role of atomic H* in activating hydrogen peroxide to produce singlet oxygen for emerging organic contaminants degradation - Xixi Chen; Wanyi Fu; Yulong Yang; Yanjun Li; Kai Yang; Xuanbo Xu; Xihui Zhang (Journal of Environmental Chemical Engineering, 2023)

Effect of Cu loading content on the catalytic performance of Cu-USY catalysts for selective catalytic reduction of NO with NH3 - Jie Wan; Haipeng Yang; Yijun Shi; Yanjun Liu; Jin Zhang; Jun Zhang; Gongde Wu; Renxian Zhou (Journal of Environmental Sciences, 2023)

Diversified chemical profiles of cuticular wax on alpine meadow plants of the Qinghai-Tibet Plateau - Jianfeng Yang; Lucas Busta; Reinhard Jetter; Yingpeng Sun; Tianyu Wang; Wenlan Zhang; Yu Ni; Yanjun Guo (Planta, 2023)

Can the marketization of urban land transfer improve energy efficiency? - Yanjun Yang; Rui Xue; Xiaoxi Zhang; Yutai Cheng; Yuli Shan (Journal of Environmental Management, 2023)

The regulatory roles of DDIT4 in TDCIPP-induced autophagy and apoptosis in PC12 cells - Li Li; Lingyi Xi; Jin Wu; Zunquan Zhao; Youliang Chen; Weili Liu; Zhihui Pan; Mingzhu Liu; Danfeng Yang; Zhaoli Chen; Yanjun Fang (Journal of Environmental Sciences, 2023)

Microwave heating instead of blanching to produce low-fat French fries - Cheng Zhang; Xiaomei Lyu; Rana Muhammad Aadil; Yanjun Tong; Wei Zhao; Ruijin Yang (Innovative Food Science & Emerging Technologies, 2023)

Characterization of physical properties, volatile compounds and aroma profiles of different salted egg yolk lipids - Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Wen Xiong; Yujie Su; Yanjun Yang (Food Research International, 2023)

Pulsed electric field as a promising technology for solid foods processing: A review - Cheng Zhang; Xiaomei Lyu; Rai Naveed Arshad; Rana Muhammad Aadil; Yanjun Tong; Wei Zhao; Ruijin Yang (Food Chemistry, 2023)

Enhanced H2O2 utilization efficiency in Fenton-like system for degradation of emerging contaminants: Oxygen vacancy-mediated activation of O2 - Xixi Chen; Wanyi Fu; Zhichao Yang; Yulong Yang; Yanjun Li; Hui Huang; Xihui Zhang; Bingcai Pan (Water Research, 2023)

Low-intensity pulsed ultrasound promotes proliferation and myelinating genes expression of Schwann cells through NRG1/ErbB signaling pathway - Bo Huang; Yixuan Jiang; Liang Zhang; Bo Yang; Yanjun Guo; Xingmei Yang; Ping Gong (Tissue and Cell, 2023)

Applications of Computed Tomography (CT) in environmental soil and plant sciences - Huan Zhang; Hailong He; Yanjun Gao; Ahmed Mady; Vilim Filipović; Miles Dyck; Jialong Lv; Yang Liu (Soil and Tillage Research, 2023)

Using one-dimensional convolutional neural networks and data augmentation to predict thermal production in geothermal fields - Yunxing Yang; Yanjun Zhang; Yuxiang Cheng; Zhihong Lei; Xuefeng Gao; Yibin Huang; Yueqiang Ma (Journal of Cleaner Production, 2023)

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Construction of g-C3N4 with three coordinated nitrogen (N3C) vacancies for excellent photocatalytic activities of N2 fixation and H2O2 production - Yanjun Xue; Chaoqun Ma; Qingfeng Yang; Xinyu Wang; Shanna An; Xiaoli Zhang; Jian Tian (Chemical Engineering Journal, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.

Development and application of a 6000-meter double decelerating lander - Lei Guo; Xiuqing Yang; Gang Xue; Cheng Wang; Zihang Fei; Shaotong Zhang; Yanjun Liu; Kai Lu; Yuan Yang (Frontiers in Marine Science, 2023)
The deep-sea lander is an important equipment for in-situ detection and monitoring. It is of great significance to understand the benthic boundary layer’s physical, chemical, and ecological environment. A 6000-meter double decelerating lander was created to meet the deployment requirements of underwater detection and monitoring, allowing for long-term in-situ monitoring of several benthic boundary layer components. Protection of the installed ocean bottom seismometer (OBS) is required due to the lander’s and OBS’s different impact resistances. The double decelerating unit enables the OBS to avoid colliding with the seabed when the lander lands and then collides with the seabed at a slow speed rather than the speed at which the lander falls, which is intended to safeguard OBS from damage. To ensure a safe deployment, the lander’s static analysis and simulation were performed using ANSYS, and the motion characteristics of the application process were derived. Numerous data have been obtained after the lander’s successful application in the South China Sea. The lander provides an investigation approach for marine science and geochemistry, complementing a technical approach to marine environmental investigations.

A brief review on deer keds of the genus Lipoptena (Diptera: Hippoboscidae) - Nouhoum Dibo; Yanjun Yang; Xiang Wu; Fanming Meng (Veterinary Parasitology, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Spatially resolved broadband absorption spectroscopy measurements of temperature and multiple species (NH, OH, NO, and NH 3 ) in atmospheric-pressure premixed ammonia/methane/air flames - Xinyu Yang; Zhimin Peng; Yanjun Ding; Yanjun Du (Fuel, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

High performance Na3V2(PO4)3 with nitrogen-chlorine co-doped carbon matrix in-situ synthesized in chitosan quaternary ammonium hydrogel for sodium ion batteries - Jiahao Li; Yanjun Chen; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Unravelling the regulation mechanism of nanoflower shaped Na3V2(PO4)3 in methanol–water system for high performance sodium ion batteries - Shiqi Sun; Yanjun Chen; Qiang Bai; Zhen Tian; Que Huang; Changcheng Liu; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Experimental and modeling investigation of freezing characteristic curve of silty clay using TDR - Quanming Xin; Yanjun Su; Yang Cao; Xiaokang She; Zhihui Wang; Xianzhang Ling; Tianhong Yang (Cold Regions Science and Technology, 2023)

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Immunomodulatory Function of Egg White Peptides in RAW264.7 Macrophage Cells and Immunosuppressive Mice Induced by Cyclophosphamide - Fan Zhang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (International Journal of Peptide Research and Therapeutics, 2022)

Flotation de-inking for recycling paper: contrasting the effects of three mineral oil-free offset printing inks on its efficiency - Shujie Yang; Jianbin Shen; Tiefei He; Chao Chen; Junming Wang; Yanjun Tang (Environmental Science and Pollution Research, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Particle size effects in microbial characteristics in thermophilic anaerobic digestion of cattle manure containing copper oxide - Yuanyuan Lu; Xuna Liu; Yanjun Miao; Efthalia Chatzisymeon; Lina Pang; Luqing Qi; Ping Yang; Hongyan Lu (Environmental Science and Pollution Research, 2022)

Effects of inhomogeneity on mechanical properties of granites in Songliao Basin using the grain-based model - Tianrui Yang; Ziwang Yu; Yanjun Zhang; Jianguo Kang; Xiaoqi Ye; Chaohui Yan (Arabian Journal of Geosciences, 2022)

CircLPAR3 Acts as an Oncogene in Oral Squamous Cell Carcinoma Through Regulating the miR-643/HMGB2 Network - Yunxia Fu; Chunyan Qiu; Yanjun Yang; Jianying Lu; Yun Qi (Biochemical Genetics, 2022)

The edited UPF1 is correlated with elevated asparagine synthetase in pancreatic ductal adenocarcinomas - Jiayang Hu; Zhen Wang; Shunchao Yang; Yanjun Lu; Gang Li (Molecular Biology Reports, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Molecular phylogenetics and evolutionary history of Sinocyclocheilus (Cypriniformes: Cyprinidae) species within Barbinae in China - Na Yang; Yingwen Li; Zhihao Liu; Qiliang Chen; Yanjun Shen (Environmental Biology of Fishes, 2021)

Research on Optimization and Verification of the Number of Stator Blades of kW Ammonia Working Medium Radial Flow Turbine in Ocean Thermal Energy Conversion - Yun Chen; Yanjun Liu; Wei Yang; Yiming Wang; Li Zhang; Yongpeng Wu (Journal of Marine Science and Engineering, 2021)
Ocean Thermal Energy Conversion (OTEC) is one of the emerging industries of ocean energy and an important link in carbon neutrality. Turbine is a key component of ocean thermal energy conversion, which has an important impact on the performance and energy conversion efficiency of the system. This paper fully considers the application characteristics of ocean thermal energy conversion and the state conversion characteristics of ammonia working fluid. Taking the 100 kW radial inflow turbine in the OTEC application system as an example, based on the design, the turbine is optimized for the key parameters of the turbine stator and the influence of different geometric parameters is analyzed. Subsequently, the optimization results are verified by CFD numerical simulation analysis under different conditions. The results show that the number of stator blades has an important influence on the performance of the turbine. Further optimization studies have shown that through optimization, when the number of stator blades is 33, the internal flow field performance is the best, and the working conditions of the inlet and outlet working fluids are in accordance with the design points without obvious shock wave and reverse flow phenomenon, the efficiency is 89.46%, 3.94% higher than the design value.

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Inversion of tight oil origin by geochemical characteristics: a case study of central Northern Shaanxi Slope, Ordos Basin - Xindi Shao; Shijia Chen; Junjie Lei; Yanjun Bai; Kai Zhou; Yang Liu; Jiang Zhu; Meimei Han (Arabian Journal of Geosciences, 2021)

Three-Dimensional Performance Analysis of a Radial-Inflow Turbine for Ocean Thermal Energy Conversion System - Yun Chen; Yanjun Liu; Li Zhang; Xiaowei Yang (Journal of Marine Science and Engineering, 2021)
Turbine is one of the key components of the ocean thermal energy conversion system (OTEC), and its aerodynamic performance and geometric dimension affect the performance of the system directly. This paper proposes a design method for the radial inflow turbine suitable for the ocean thermal energy conversion based on the parameter optimization of the ocean thermal energy conversion system. Aiming at the application characteristics of marine thermal energy conversion in a small temperature difference environment and the special thermophysical properties of the organic working fluid in this environment, one-dimensional design and three-dimensional CFD analysis of the turbine is separately done, of which the results were compared. At the same time, the performance of the turbine was verified by changing the inlet and outlet conditions of the radial turbine under the design conditions. The conclusion is that the three-dimensional CFD results of the turbine are in good agreement with the one-dimensional design, and the internal flow field of the turbine is stable, without obvious backflow and eddy current, which meets the application requirements of the ocean thermal energy conversion.

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Effectiveness of predicting spatial contaminant distributions at industrial sites using partitioned interpolation method - Pengwei Qiao; Sucai Yang; Wenxia Wei; Peizhong Li; Yanjun Cheng; Shuang Liang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2021)

Interspecific competition between Cylindrospermopsis raciborskii and Microcystis aeruginosa on different phosphorus substrates - Fang Bai; Junqiong Shi; Songqi Yang; Yanjun Yang; Zhongxing Wu (Environmental Science and Pollution Research, 2020)

mRNA and microRNA Profiles in the Amygdala Are Relevant to Susceptibility and Resilience to Psychological Stress Induced in Mice - Jinyan Sun; Yanjun Lu; Jiuyong Yang; Zhenhua Song; Wei Lu; Jin-Hui Wang (Journal of Molecular Neuroscience, 2020)

Application of deep learning in ecological resource research: Theories, methods, and challenges - Qinghua Guo; Shichao Jin; Min Li; Qiuli Yang; Kexin Xu; Yuanzhen Ju; Jing Zhang; Jing Xuan; Jin Liu; Yanjun Su; Qiang Xu; Yu Liu (Science China Earth Sciences, 2020)

Correction to: mRNA and microRNA profiles are associated with stress susceptibility and resilience induced by psychological stress in the prefrontal cortex - Jiuyong Yang; Jinyan Sun; Yanjun Lu; Tingting An; Wei Lu; Jin-Hui Wang (Psychopharmacology, 2020)

Revision to psychopharmacology mRNA and microRNA profiles are associated with stress susceptibility and resilience induced by psychological stress in the prefrontal cortex - Jiuyong Yang; Jinyan Sun; Yanjun Lu; Tingting An; Wei Lu; Jin-Hui Wang (Psychopharmacology, 2020)

Population genetic divergence in Lycium chinense Mill. (Solanaceae) is driven by both hybridization and geo-environmental factors - Lulu Yang; Yan He; Shuhui Wang; Yanjun Zhang; Ying Wang; Qiong Liang (Genetic Resources and Crop Evolution, 2020)

The treatment and follow‐up of ‘recurrence’ with discharged COVID ‐19 patients: data from Guizhou, China - Maolu Tian; Yanjun Long; Yang Hong; Xiangyan Zhang; Yan Zha (Environmental Microbiology, 2020)
Summary We reported 20 cases of discharged COVID‐19 patients whose RT‐PCR test results showed ‘re‐positive’. After finding ‘re‐positive’, these patients were admitted to hospital for the second time and were followed up until the end of May 2020. We recorded detailed treatment and follow‐up process, and collected relevant data. The possible causes and potential clinical significance of this phenomenon are discussed.

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil - Zhibin He; Luhua Yao; Xuefeng Zhang; Yang Li; Dengke Wang; Lin Kang; Cui Cui; Aiying Huang; Ruiji Yang; Qianlin Xiao; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2020)

The complete mitochondrial genome of Cobitis macrostigma (Cypriniformes: Cobitidae: Cobitinae) and a phylogenetic implication for its closely related species - Na Yang; Yingwen Li; Zhihao Liu; Qiliang Chen; Yanjun Shen (Biologia, 2020)

Influence of Pore Water (Ice) Content on the Strength and Deformability of Frozen Argillaceous Siltstone - Hailiang Jia; Fan Zi; Gengshe Yang; Guoyu Li; Yanjun Shen; Qiang Sun; Pengyu Yang (Rock Mechanics and Rock Engineering, 2020)

Comparison of common spatial interpolation methods for analyzing pollutant spatial distributions at contaminated sites - Pengwei Qiao; Peizhong Li; Yanjun Cheng; Wenxia Wei; Sucai Yang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2019)

Rising grain prices in response to phased climatic change during 1736–1850 in the North China Plain - Yanjun Wen; Xiuqi Fang; Yang Liu; Yikai Li (Science China Earth Sciences, 2019)

High mineral adsorption of glyphosate versus diethyl phthalate and tetracycline, during visible light photodegradation with goethite and oxalate - Zhengfang Zhang; Zhuozhi Ouyang; Jingjing Yang; Yanjun Liu; Chen Yang; Zhi Dang (Environmental Chemistry Letters, 2019)

Interannual relationship between intensity of rainfall intraseasonal oscillation and summer-mean rainfall over Yangtze River Basin in eastern China - Yanjun Qi; Tim Li; Renhe Zhang; Yang Chen (Climate Dynamics, 2019)

Expression profile of circular RNAs in myocardial ischemia/reperfusion with and without intermittent hypobaric hypoxia preconditioning - Jiliang Tan; Shanshan Gu; Yanjun Zheng; Huangtian Yang (Science China Life Sciences, 2019)

Change of winter wheat planting area and its impacts on groundwater depletion in the North China Plain - Xifang Wu; Yongqing Qi; Yanjun Shen; Wei Yang; Yucui Zhang; Akihiko Kondoh (Journal of Geographical Sciences, 2019)

Cloning, Expression, and Bioinformatics Analysis of Heavy Metal Resistance Gene afe_1862 from Acidithiobacillus ferrooxidans L1 in Escherichia coli - Feifan Leng; Yuanli Li; Wen Luo; Qingwei Wei; Yanjun Jing; Xiaoli Wang; Mingjun Yang; Yonggang Wang (Biological Trace Element Research, 2019)

How up-scaling of remote-sensing images affects land-cover classification by comparison with multiscale satellite images - Kaijian Xu; Qingjiu Tian; Yanjun Yang; Jibo Yue; Shaofei Tang (International Journal of Remote Sensing, 2019)

Transplantation of umbilical cord–derived mesenchymal stem cells on a collagen scaffold improves ovarian function in a premature ovarian failure model of mice - Yanjun Yang; Lei Lei; Shanshan Wang; Xiaoqiang Sheng; Guijun Yan; Lu Xu; Jingyu Liu; Mengyuan Liu; Xin Zhen; Lijun Ding; Haixiang Sun (In Vitro Cellular & Developmental Biology - Animal, 2019)

Rural solid waste—characteristics and leachate pollution assessment for different precipitation levels, China - Huiyuan Yang; Bo Yue; Yanjun Liu; Xiaohui Wu; Hong Gao; Zhibin Zhang; Zhuoyi Yan (Environmental Science and Pollution Research, 2019)

Developing a comprehensive evaluation method for Interconnected River System Network assessment: A case study in Tangxun Lake group - Wei Yang; Liping Zhang; Yanjun Zhang; Zongli Li; Yi Xiao; Jun Xia (Journal of Geographical Sciences, 2019)

Biochar reduces cadmium accumulation in rice grains in a tungsten mining area-field experiment: effects of biochar type and dosage, rice variety, and pollution level - Min Zhang; Shengdao Shan; Yonggen Chen; Fang Wang; Deyi Yang; Jikai Ren; Haoyu Lu; Lifeng Ping; Yanjun Chai (Environmental Geochemistry and Health, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)

Glyphosate application increased catabolic activity of gram-negative bacteria but impaired soil fungal community - Yehao Liu; Yongchun Li; Xiaomei Hua; Karin Müller; Hailong Wang; Tongyi Yang; Qiong Wang; Xin Peng; Mengcheng Wang; Yanjun Pang; Jinliang Qi; Yonghua Yang (Environmental Science and Pollution Research, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Calreticulin protects the HT22 hippocampal neurons from injury induced by hypoxia - Zhaoping Wang; Mei Yang; Jian Xue; Yanjun Chong (Molecular & Cellular Toxicology, 2018)

Ectopic expression of cucumber (Cucumis sativus L.) CsTIR/AFB genes enhance salt tolerance in transgenic Arabidopsis - Zhehao Chen; Mengting Li; Ye Yuan; Jiangqin Hu; Yanjun Yang; Jiliang Pang; Lilin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Transcription factor Sp1 is necessary and functional in regulating expression of oncogene ZNF703 - Xiaolin Liao; Yongjie Lu; Junbao Yang; Tao Kuang; Lilin Jiang; Yanjun Wang; Huiqun Kang; Bo Jiang; Xiaoli Zhou; Sheng He (Genes & Genomics, 2017)

Pharmacokinetics and immunogenicity of T0001, a newly developed anti-TNFα fusion protein, in healthy volunteers - Yitong Wang; Chang Liu; Shi Chen; Wei Wang; Lihou Dong; Qian Wang; Yan Wang; Libo Zhao; Yannan Zang; Zhenwei Xie; Yang Liu; Yanjun Liu; et al. (European Journal of Clinical Pharmacology, 2017)

Two new coumarins from the bark of Streblus indicus (Bur.) Corner - Ruijie He; Shengping Deng; Hui Nie; Yan Huang; Buming Liu; Ruiyun Yang; Shuai Huang; Dexiong Zhou; Huangcan Chen; Jun Li; Yanjun Zhang (Natural Product Research, 2017)

Transcriptome analysis reveals that constant heat stress modifies the metabolism and structure of the porcine longissimus dorsi skeletal muscle - Yue Hao; Yuejin Feng; Peige Yang; Yanjun Cui; Jiru Liu; Chunhe Yang; Xianhong Gu (Molecular Genetics and Genomics, 2016)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

The response and detoxification strategies of three freshwater phytoplankton species, Aphanizomenon flos-aquae, Pediastrum simplex, and Synedra acus, to cadmium - Xiaofei Ran; Hong Yue; Xiaoli Fu; Yuanhao Kang; Sha Xu; Yanjun Yang; Jinzhu Xu; Junqiong Shi; Zhongxing Wu (Environmental Science and Pollution Research, 2015)

Auxin signaling is involved in iron deficiency-induced photosynthetic inhibition and shoot growth defect in rice (Oryza sativa L.) - Kaidong Liu; Runqing Yue; Changchun Yuan; Jinxiang Liu; Lei Zhang; Tao Sun; Yanjun Yang; Shuanggui Tie; Chenjia Shen (Journal of Plant Biology, 2015)

Spatiotemporal variability of winter wheat phenology in response to weather and climate variability in China - Dengpan Xiao; Juana P. Moiwo; Fulu Tao; Yonghui Yang; Yanjun Shen; Quanhong Xu; Jianfeng Liu; He Zhang; Fengshan Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Novel integration strategy coupling codon and fermentation optimization for efficiently enhancing sarcosine oxidase (SOX) production in recombinant Escherichia coli - Yanjun Tong; Hailin Yang; Yu Xin; Ling Zhang; Wu Wang (World Journal of Microbiology and Biotechnology, 2015)

Assessment of growth rate, chlorophyll a fluorescence, lipid peroxidation and antioxidant enzyme activity in Aphanizomenon flos-aquae, Pediastrum simplex and Synedra acus exposed to cadmium - Xiaofei Ran; Rui Liu; Sha Xu; Fang Bai; Jinzhu Xu; Yanjun Yang; Junqiong Shi; Zhongxing Wu (Ecotoxicology, 2015)

Deposition rate and interaction of human-riverine from height increase and permanent function of an 1180 years weir in Southeast China - YanJun Shang; Hyeong-Dong Park; ZhiFa Yang; SiGuang Chen; DaMing Lin (Science China Earth Sciences, 2014)

Application of exogenous substances reduces tobacco-specific nitrosamines content by regulating biosynthesis of nicotine and nitrite in burley tobacco - Siwei Liang; Jinpeng Yang; Jun Zhou; Jun Yu; Yanjun Ma; Ruoshi Bai; Fangsen Xu; Chunlei Yang (Acta Physiologiae Plantarum, 2013)

Control of the PI3K/Akt pathway by porcine reproductive and respiratory syndrome virus - Liqian Zhu; Shen Yang; Wu Tong; Jianping Zhu; Hai Yu; Yanjun Zhou; Robert B. Morrison; Guangzhi Tong (Archives of Virology, 2013)

LC determination and pharmacokinetic study of the main phenolic components of Portulaca oleracea L. extract in rat plasma after oral administration - Zhongzhe Cheng; Dong Wang; Wenjie Zhang; Yang Du; Yunjiao Wang; Yanjun Zhai; Xixiang Ying; Tingguo Kang (Natural Product Research, 2012)

Biodegradable Polymer-Curcumin Conjugate Micelles Enhance the Loading and Delivery of Low-Potency Curcumin - Rulei Yang; Suai Zhang; Deling Kong; Xuli Gao; Yanjun Zhao; Zheng Wang (Pharmaceutical Research, 2012)

β-Arrestin prevents cell apoptosis through pro-apoptotic ERK1/2 and p38 MAPKs and anti-apoptotic Akt pathways - Xiaohua Yang; Gengyin Zhou; Tao Ren; Hui Li; Yanjun Zhang; Deling Yin; Haixin Qian; Qinchuan Li (Apoptosis, 2012)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

RfaB, a galactosyltransferase, contributes to the resistance to detergent and the virulence of Salmonella enterica serovar Enteritidis - Jing Su; Dommo Timbely; Minmin Zhu; Xiaomei Hua; Biao Liu; Yanjun Pang; Hengguan Shen; Jinliang Qi; Yonghua Yang (Medical Microbiology and Immunology, 2009)

Flexible design of a rock slope abutment at the Wuqiangxi Hydroelectric Power Station - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang; Da’an Liu; Chunhua Tang (Bulletin of Engineering Geology and the Environment, 2006)

Engineering geological zonation using interaction matrix of geological factors: An example from one section of Sichuan-Tibet Highway - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang (Geosciences Journal, 2005)

Seasonal variation of sedimentation in the Changjiang Estuary mud area - Guo Zhigang; Yang Zuosheng; Fan Dejiang; Pan Yanjun (Journal of Geographical Sciences, 2003)